Pre-service mathematical teachers' knowledge of different teaching methods of the limit and continuity concept - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study aims at examining pre-service teachers' knowledge of different teaching methods for the concept of limit and continuity in functions. To gather data, a questionnaire was administered to 37 pre-service teachers studying in the last year of Secondary School Mathematics Education and semi-structured interviews were conducted with 4 pre-service teachers. From the results of the study, it can be concluded that the present teacher training program has some deficiencies in providing pre-service teachers to integrate different teaching methods into their teaching. In other words, the practical aspect of the program is not as powerful as its theoretical aspect. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Pedagogical content knowledge; concept of limit and continuity; teacher training; mathematics education